Le Dasavatthuppakarana: Edited and translated by Jacqueline Ver Eecke. - Webb, Russell (Buddhist Studies Review, 1980)
Le Dasavatthuppakarana: Edited and translated by Jacqueline Ver Eecke. Publications de l'Ecole Francaise d'Extreme-Orient, Paris, 1976. Distributed by Adrien-Maisonneuve, 11 rue Saint Sulpice, F-75006 Paris. xvi + 155 pp. Fcs. 65.00